The Impact of International Migration on Inclusive Growth : A Review. (IMF Working Papers; Working Paper ;, 2021)
International migration is an important channel of material improvement for individuals and their offspring. The movement of people across country borders, especially from less developed to richer countries, has a substantial impact in several dimensions. First, it affects the migrants themselves by allowing them to achieve higher income as a result of their higher productivity in the destination country. It also increases the expected income for their offspring. Second, it affects the destination country through the impact on labor markets, productivity, innovation, demographic structure, fiscal balance, and criminality. Third, it can have a significant impact on the countries of origin. It may lead to loss of human capital, but it also creates a flow of remittances and increases international connections in the form of trade, FDI, and technological transfers. This paper surveys our understanding of how migration affects growth and inequality through the impact on migrants themselves as well as on the destination and origin countries.